Investigation of sodium storage in manganese vanadate MnV2O6 nanobelt and nanoparticle as an anode for sodium-ion batteries. (20th January 2021) - Kim, Kyeong-Ho; Hong, Seong-Hyeon
Highlights: Electrochemical reaction mechanism of MnV2 O6 as an anode for SIBs is investigated. Electrochemical performance of MnV2 O6 nanobelt and nanoparticle is compared. MnV2 O6 nanobelt electrode shows better cycle retention and long-term cyclability. Abstract: Manganese vanadate (MnV2 O6 ) nanobelts (MVO-NBs) and nanoparticles (MVO-NPs) with a brannerite structure are synthesized by hydrothermal and high energy mechanical milling methods, respectively, and their electrochemical properties as an anode for sodium-ion batteries (SIBs) are investigated. Ex-situ X-ray diffraction (XRD) and X-ray absorption spectroscopy (XAS) studies indicate that MnV2 O6 is transformed to a low crystalline phase during the first sodiation without a further amorphization, which is different from MnV2 O6 /Li cell and results in a relatively low reversible capacity in MnV2 O6 /Na cell. The MVO-NB electrode exhibits the better electrochemical performance than MVO-NP electrode, possibly due to the fast diffusion kinetics resulting from the short diffusion length. The MVO-NB electrode shows a stable long-term cycle stability, delivering a reversible capacity of 110 mA h g −1 after 1000 cycles at a high current density of 500 mA g −1 . Graphical abstract: The MnV2 O6 nanobelt electrode is electrochemically active with sodium ion showing an excellent cycle retention with a high Coulombic efficiency. Image, graphical abstract